Nursing students perceptions and experiences of high fidelity simulation as a learning and teaching strategy in a resource limited setting - Munangatire, Takaedza (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2014.